The influence of a management style on the psychological mental bornout of municipal services employees - FILATOVA, OLGA; FILATOV, VITALIY; SEMENOVA, ALENA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2016)
The article investigates to the nature of the influence of management style on the formation and development of mental burnout among municipal employees.